Studies on Hydrogenation of Liquid Natural Rubber Using Diimide - Nur Hanis Adila Azhar; Naharullah Jamaluddin; Hamizah Md Rasid; Muhammad Jefri Mohd Yusof; Siti Fairus M. Yusoff (International Journal of Polymer Science)
Liquid natural rubber (LNR) is a depolymerized natural rubber (NR) which consists of shorter polymeric chains and lower molecular weight (Mw<105). Hydrogenated LNR (HLNR) was synthesized via the thermal decomposition of p-toluenesulfonyl hydrazide (TSH) or 2,4,6-trimethylbenzenesulfonyl hydrazide (MSH). The LNR and HLNR structures were characterized by Fourier-transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies. The percentage of hydrogenation was calculated from NMR spectrum. The optimum percentage of hydrogenation (>90%) was achieved by manipulating the reaction parameters such as sources of diimide, TSH concentration, solvent, and reaction time. The optimum condition was 3 : 1 weight ratio of TSH/LNR in o-xylene at 130°C in 4-hour reaction period.